Promoting higher-order thinking skills during online learning: The integration of metacognition in science for higher education - Ika Maryani; Zuhdan Kun Prasetyo; Insih Wilujeng; Siwi Purwanti (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to explore the integration of metacognition in online science education for college students and tested the feasibility of the learning model on students’ high order thinking skills (HOTS). The analyze, design, develop, implement, and evaluate (ADDIE) model was employed in this study. A needs analysis was conducted through interviews and questionnaire surveys to 21 science lecturers from primary school teacher education study programs at seven state universities and 14 private universities in Indonesia. In the development phase, the effectiveness of the model was examined through an experimental study involving three groups of students: experimental group (41 students), control group 1 (39 students), and control group 2 (39 students). The experimental study was performed using the randomized pretest-posttest comparison group design. The research hypothesis was investigated using a general linear model and multivariate analysis of variance. Through awareness-building, essential questioning, planning, monitoring, evaluating, and reflecting, this study successfully integrated metacognition into online science education. The model's learning syntax incorporated both synchronous and asynchronous learning activities. Virtual and contextual projects are critical components of this approach because they demonstrate how metacognition is regulated. Expert judgment indicated that the model under development was highly feasible. The experimental study established that the learning model had a considerable effect on students’ HOTS, which rose by 75% (a large effect) due to the model’s implementation.